Solving the evolutionary puzzle of human cooperation - Barenthin, Glenn (Scientific studies of religion: inquiry and explanation, 2020)
Minds, gods and group selection theory -- A modest proposal -- Family matters -- From thin to thick cooperation -- How does that make sense? -- The road to Denmark.